Hello everyone,

I need some help with the following ordinary differential equation:

y'=(2y-x)/(2x-y), and y(2)=3

and I also have to solve it for y(0)=0 and explain what happens exactly.

I'll appreciate any help.

Printable View

- Oct 30th 2010, 08:38 AMGIPCHelp with a basic equation
Hello everyone,

I need some help with the following ordinary differential equation:

y'=(2y-x)/(2x-y), and y(2)=3

and I also have to solve it for y(0)=0 and explain what happens exactly.

I'll appreciate any help. - Oct 30th 2010, 08:50 AMJhevon
this is homogenious.

note that you have $\displaystyle \displaystyle \frac {dy}{dx} = \frac {2 \frac yx - 1}{2 - \frac yx}$

Let $\displaystyle \displaystyle v = \frac yx \implies y = vx \implies \frac {dy}{dx} = x \frac {dv}{dx} + v$

So your equation becomes:

$\displaystyle \displaystyle x \frac {dv}{dx} + v = \frac {2v - 1}{2 - v}$

Now that equation is separable. continue... - Oct 30th 2010, 09:59 AMGIPC
let me see if I got it right.

I get

x*dv=(v^2-1)/(2-v) dx

I integrate both sides and get

x*v=[(v^2-1)/(2-v)]*x +C

using v=y/x

y=...=[y^2-x^2]/(2x^2-xy) + C

now what do I do from here? - Oct 30th 2010, 10:07 AMJhevon
- Oct 30th 2010, 10:38 AMGIPC
how about this then

we reverse the sides and get

(2-v)/(v^2-1) dv = dx/x

integrate and get

1/2[ln(1-v) - 3ln(v+1)]= lnx +C

so

ln[(1-y/x)/(y/x+1)^3]=2lnx+2c

(1-y/x)/[(y/x+1)^3]=x*e^2c

what shoud i do from here? - Oct 30th 2010, 11:36 AMJhevon
Lets take it from $\displaystyle \displaystyle \ln \left| \frac {v - 1}{(v + 1)^3} \right| = 2 \ln |x| + C = 2 \ln |Ax| = \ln (Ax)^2$

Then we have

$\displaystyle \displaystyle \frac {v - 1}{(v + 1)^3} = (Ax)^2$

$\displaystyle \displaystyle \Rightarrow \frac {\frac yx - 1}{\left( \frac yx + 1 \right)^3} = (Ax)^2$

multiply the left side by $\displaystyle \displaystyle \frac {x^3}{x^3}$ to get

$\displaystyle \displaystyle \frac {x^2y - x^3}{(y + x)^3} = (Ax)^2$

divide both sides by $\displaystyle \displaystyle x^2$ to get

$\displaystyle \displaystyle \frac {y - x}{(y + x)^3} = A^2$

Plug in your initial data: $\displaystyle \displaystyle y(2) = 3$ and solve for $\displaystyle \displaystyle A$. you end up with

$\displaystyle \displaystyle \frac {y - x}{(y + x)^3} = \frac 1{125}$

that's your solution, defined implicitly.